Changing Perspectives on the Planning of Ankara (1924-2007) and Lessons for a New Master-Planning Approach to Developing Cities - Olgu Çalişkan (Footprint)
As one of the newly planned capitals in the 20th century – like Islamabad, Canberra and Brazil –, Ankara represents an original case in planning history: from shaping a new town under the influence of early European urbanism to the control of a dynamic metropolitan form by structural planning approaches. Forming its urban core according to the initial planning perspectives between the beginning of 1930s and the mid-1970s, the city has entered a rapid phase of space production in its extensions for about the last thirty years.